Neonatal kerion celsi superimposed on atopic dermatitis. - Aba, F.C.; Çalıcıoğlu, F. (European Journal of Pediatric Dermatology, 2025)
Kerion celsi is a deep fungal infection subtype involving hair follicular units, predominantly affecting children aged 3 to 7 years. This condition is rarely documented in infancy. Systemic terbinafine, combined with topical antifungal agents, may represent a safe and effective therapeutic option in early infancy. Atopic dermatitis is a chronic inflammatory disease that increases the risk of bacterial, viral, and fungal infections. Moreover, it’s a recognized risk factor that can exacerbate the severity of fungal infections. These conditions may co-occur in the presence of immune deficiency syndromes, particularly in early childhood. Co-existing cases with suspected immunodeficiency necessitate thorough investigation to ensure accurate diagnosis and optimal management. This case report aims to present therapeutic approaches employed in the treatment of an infant diagnosed with kerion celsi and moderate atopic dermatitis.